Effect of Education and Literacy on Consistency of Responses to Upper-Extremity Patient-Reported Outcome Measures - Zama, Roland; Clark, Desraj M; Iskandarova, Aygul; Yohe, Gabriel J; Azad, Chao Long; Giladi, Aviram M (The Journal of hand surgery (American ed.), 2025)
The Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) and Patient-Reported Outcomes Measurement Information System Upper Extremity (PROMIS-UE) are frequently used upper-extremity patient-reported outcome measures (PROMS). There are mixed findings regarding reliability across different administration formats. The impact of education and literacy on PROM response consistency remains underexplored. We evaluated whether education and literacy levels are associated with variability in QuickDASH and PROMIS-UE responses between written and audio administration. We recruited adults with a high school diploma/general educational diploma ("higher education") or less ("lower education") and evaluated their literacy with the Rapid Estimate of Adult Literacy in Medicine instrument. All participants completed written versions of QuickDASH and PROMIS-UE and then audio-administered versions. We compared consistency between written and audio responses, focusing on differences in responses to individual questions ("discrepancy"). When adequately powered to do so, we compared subgroups using independent t tests. We included 114 participants, of whom 95 had higher education and 19 had lower education. Discrepancy for PROMIS-UE between audio and written administration was considerably greater in the lower education cohort (lower education average discrepancy of 4.4 questions vs 1.8 in the higher education group). The QuickDASH had similar findings (lower education average discrepancy of 5.1 questions vs 3.4 in the higher education cohort). Discrepancy for low literacy patients was 2.4 questions (PROMIS-UE) and 3.9 questions (QuickDASH), and 2.1 (PROMIS-UE) and 3.6 (QuickDASH) for high literacy patients. Patients with lower educational attainment showed greater variability in PROM responses between written and audio formats. Additional sufficiently powered studies are needed to determine whether this is also true for patients with lower literacy levels. Because education level influences consistency of PROM responses, it is important to consider alternative administration methods, such as audio, to ensure accurate patient-reported outcome data collection.